The Effect Efektivitas Modal Investasi dan Sumber Daya Manusia dalam Meningkatkan Kinerja Ekonomi Kota Medan 2005-2024 - Samuel Sihite; Irsad Lubis (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the effect of regional investment and labor force on economic growth in Medan City from 2005 to 2024. The research background emphasizes the crucial role of investment and labor as key components in achieving sustainable regional economic development. The study employed a quantitative method using multiple linear regression analysis with the SPSS application. Secondary data were obtained from the Central Statistics Agency (BPS) over the past two decades. The results show that, partially, regional investment has a significant effect on economic growth with a contribution of 31.2%, while the labor force contributes 18.4%. Simultaneously, both variables jointly explain 60.5% of the variation in Medan’s economic growth. These findings reinforce previous studies, indicating that regional economic growth strongly depends on the synergy between capital accumulation and labor capacity. Therefore, regional development policies should focus on strengthening productive investments and improving human resource quality to ensure sustainable economic growth.